1998
DOI: 10.1086/514620
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacodynamics of Aminoglycosides

Abstract: Recently, a more complete understanding of the pharmacodynamics of aminoglycosides has been recognized, indicating that this class of antibiotics exhibits both concentration-dependent bactericidal activity and a postantibiotic effect. This pharmacodynamic information, along with better knowledge of the mechanisms responsible for aminoglycoside toxicity, established the foundation for once-daily aminoglycoside dosing regimens. This new approach to aminoglycoside dosing appears to be safe, efficacious, and cost-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
135
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(140 citation statements)
references
References 46 publications
2
135
0
3
Order By: Relevance
“…Previous studies have repeatedly demonstrated a concentration-dependent killing effect of aminoglycosides against Gram-negative bacteria. [7][8][9][10] The uptake of an aminoglycoside antibiotic such as gentamicin into P. aeruginosa has been recognized as a multifactorial process involving an initial ionic interaction with the exterior of the cell, followed by two energy-dependent phases requiring an energized cytoplasmic membrane. [11][12][13] One of the studies suggests that zinc has significantly increased in the MICs of imipenem for P. aeruginosa, and, to a lesser extent, for other Gram-negative bacilli in Muller-Hinton agar.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have repeatedly demonstrated a concentration-dependent killing effect of aminoglycosides against Gram-negative bacteria. [7][8][9][10] The uptake of an aminoglycoside antibiotic such as gentamicin into P. aeruginosa has been recognized as a multifactorial process involving an initial ionic interaction with the exterior of the cell, followed by two energy-dependent phases requiring an energized cytoplasmic membrane. [11][12][13] One of the studies suggests that zinc has significantly increased in the MICs of imipenem for P. aeruginosa, and, to a lesser extent, for other Gram-negative bacilli in Muller-Hinton agar.…”
Section: Discussionmentioning
confidence: 99%
“…46 As a class, aminoglycosides have concentrationdependent bactericidal activity via irreversible binding to the 30S ribosomal subunit of susceptible bacteria, inhibiting bacterial protein synthesis. 47 In vitro and clinical outcome studies 48,49 have shown that Cmax:MIC ratios of 8:1 to 10:1 maximize the bacterial killing and clinical success of aminoglycosides. In addition to their primary antibacterial effect, aminoglycosides have a postantibiotic effect: bacterial killing continues even after the concentration at the infection site (eg, blood, tissue) decreases to less than the bacterial MIC.…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…The postantibiotic effect is due to the intracellular, irreversible activity of aminoglycosides at bacterial ribosomes and ranges from 0.5 to 8 hours, depending on the C max achieved. 47,50 Aminoglycosides are hydrophilic (V d 0.2-0.3 L/kg) and doses should be based on ideal body weight or, in obese patients, on adjusted body weight. 51,52 Aminoglycosides are almost exclusively renally cleared, leading to increased urinary concentrations, a potential advantage in treating urinary tract infections.…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…In order to minimize the adverse effects of the drugs now they are commonly used once daily in contrast with the previous treatment 2-3 times per day. Given the effectiveness of these drugs is concentration-dependent and count on rapid achievement of high serum concentrations, the first dose can be injected intravenously, and the next ones -intramuscularly (Lacy et al, 1998). Well known are the nephrotoxic changes caused by these antibiotics in high doses (Hottendorf and Gordon 1980;Schentag et al, 1981) and in this respect there are comparative trials (Brion et al, 1984;Hottendorf and Gordon, 1980;Rankin et al, 1980;Schentag et al, 1981).…”
Section: Introductionmentioning
confidence: 99%